Effect of V additions on the microstructure and mechanical properties of Al-Cu-Mg-Ag alloy. (December 2022) - Ling, Kai; Chen, Junwei; Ran, Hongwei; Deng, Pan; Tang, Chenglu; Mo, Wenfeng; Ouyang, Zuoqiong; Wu, Xuekun; Luo, Binghui; Bai, Zhenhai
Abstract: The effects of V (0–0.25 wt%) addition on the microstructure and mechanical properties of Al-Cu-Mg-Ag alloys are investigated using optical microscope, tensile testing, X-ray diffraction, the electrical conductivity measurement, transmission electron microscopy and scanning electron microscopy. The present results show that the grain size of the alloys can be refined significantly by alloying V content. In addition, the alloy with 0.13 wt% V content has better mechanical properties at room temperature and at 300 ℃ than that of the alloy without V content both. With exceeded-V content (0.25 wt%), one kind of bulk phases appears, which can be identified as V2 Mg3 Al18 phase. The V2 Mg3 Al18 phase consumes the available Mg-solutes, thereby suppressing the precipitation of Ω phase, which results in the lower number density of Ω phase, and finally degrading the tensile properties at ambient temperature. However, the V2 Mg3 Al18 phase favors the mechanical properties of the Al-Cu-Mg-Ag alloy at 300 ℃. Graphical Abstract: ga1